(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Particle swarm optimization is a set of intelligent search tools used to solve suboptimal problems to reduce total inventory cost or maximize total profit. In this study, the particle swarm optimization (PSO) method was used to improve the overall results of the inventory model. Additionally, solutions for optimizing order quantity and cost effectiveness are discussed in detail. Here we consider a numerical example demonstrating the use of the design and, finally, we perform sensitivity analysis of the variable using the best product.